Effect of Cross-eye Jamming on the Active-passive Composite Monopulse Radar - Dong LI; Jin MENG; Yongcai LIU; Liang ZHOU; Binbin SU (Leida xuebao, 2022)
Cross-eye jamming is an electronic countermeasure technology used to cause angular deviation of monopulse radar via multiple coherent sources. Despite a complex electromagnetic environment, using active-passive composite monopulse radar is a development trend for improving the anti-interference ability of modern terminal guidance radar. A mathematical model of cross-eye jamming considering the active-passive composite monopulse radar is established. The influence mechanism of cross-eye jamming on the active-passive composite monopulse radar is revealed by comparing the effect of active and passive monopulse radar systems on angle measurement. Furthermore, the results can provide theoretical guidance and simulation data to reasonably apply Electronic Countermeasures (ECMs) and Electronic Counter-Countermeasures (ECCMs).